Implementation of Light Rapid Transit Transport Infrastructure Development Policy on the Development of Mass Transport in Palembang - Kartini, Sri; Komalasari, Yeti; Amanda, Monica (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The purpose of this study is to describe and analyze the implementation of policies for the development of Light Rapid Transit (LRT) transportation infrastructure in Palembang City and analyze the factors that hinder the development of Light Rapid Transit (LRT) as mass transportation in Palembang City. The research method uses the constructivism paradigm through qualitative research approaches and types with data collection techniques through observation, interviews, and documentation. The main finding in this study is the implementation of light rail transportation infrastructure development policies towards the development of mass transportation in the city of Palembang within the scope of public service standards, there are 6 (six) scopes of public service standards that must be set at least covering the fulfillment of service procedures, completion time, cost services, service products, facilities and infrastructure as well as the competence of service providers, from 6 (six) factors there are 3 (three) factors of which have been fulfilled. The novelty/originality in this study is supported by the latest observational data and studies that support the improvement of the implementation of LRT development policies in realizing the role of mass transportation in Palembang.